Analisis Problematika Pada Penggunaan Aplikasi PeduliLindungi Dalam Perspektif Hukum Nasional - Devita Triwiraputri Martinadhia (Padjadjaran Law Review, 2021)
PeduliLindungi is an application developed to assist government agencies in tracking the spread of Coronavirus Disease (COVID - 19). PeduliLindungi relies on community participation as users to inform each other of their location while traveling in order to track contact history with COVID-19 sufferers. When users download PeduliLindungi, the system will ask for user approval to activate location data. With the active location condition, the application will periodically identify the user's location and provide information regarding the crowds and zoning of the spread of COVID-19. The results of the tracking make it easier for the government to identify anyone who needs further treatment. However, in reality there are still many problems faced by users in using this application that are not in line with applicable national law. The results of the study indicate that the PeduliLindungi is still not ready to operate massively and there are also many problems as a result of using the application which is contrary to national law. Therefore, this research will examine the problems of using the PeduliLindungi and its analysis from the perspective of national law in responding to the current problems.